The Potential Use of Fly Ash from the Pulp and Paper Industry as Thermochemical Energy and CO2 Storage Material - Saman Setoodeh Jahromy; Mudassar Azam; Christian Jordan; Michael Harasek; Franz Winter (Energies, 2021)
As a part of our research in the field of thermochemical energy storage, this study aims to investigate the potential of three fly ash samples derived from the fluidized bed reactors of three different pulp and paper plants in Austria for their use as thermochemical energy (TCES) and CO2 storage materials. The selected samples were analyzed by different physical and chemical analytical techniques such as X-ray fluorescence spectroscopy (XRF), X-ray diffraction (XRD), particle size distribution (PSD), scanning electron microscopy (SEM), inductively coupled plasma atomic emission spectroscopy (ICP-OES), and simultaneous thermal analysis (STA) under different atmospheres (N2, CO2, and H2O/CO2). To evaluate the environmental impact, leaching tests were also performed. The amount of CaO as a promising candidate for TCES was verified by XRF analysis, which was in the range of 25–63% (w/w). XRD results indicate that the CaO lies as free lime (3–32%), calcite (21–29%), and silicate in all fly ash samples. The results of STA show that all fly ash samples could fulfill the requirements for TCES (i.e., charging and discharging). A cycling stability test of three cycles was demonstrated for all samples which indicates a reduction of conversion in the first three reaction cycles. The energy content of the examined samples was up to 504 kJ/kg according to the STA results. More energy (~1090 kJ/kg) in the first discharging step in the CO2/H2O atmosphere could be released through two kinds of fly ash samples due to the already existing free lime (CaO) in those samples. The CO2 storage capacity of these fly ash samples ranged between 18 and 110 kg per ton of fly ash, based on the direct and dry method. The leaching tests showed that all heavy metals were below the limit values of the Austrian landfill ordinance. It is viable to say that the valorization of fly ash from the pulp and paper industries via TCES and CO2 storage is plausible. However, further investigations such as cycling stability improvement, system integration and a life cycle assessment (LCA) still need to be conducted.